Sixth Symposium of the ICTM Study Group on Music and Minorities: July 19-25, 2010, Hanoi, Vietnam. - Jurková, Zuzana (Lidé města, 2010)
The international ethnomusicological organization the International Council for Traditional Music (ICTM) has its world conference every odd-numbered year (the most recent one took place last year in the South African city of Durban; the next one is planned for July 2011 in St. John, Canada). In the even years the majority of its study groups meet; the work in them is usually considered the main reason for the ICTM.